2021
DOI: 10.3233/jifs-189455
|View full text |Cite
|
Sign up to set email alerts
|

Research on construction method and deformation control technology of high ground stress interbedded soft rock tunnel

Abstract: The construction of tunnels is often long and deep buried tunnels, and the geological conditions are more complex. Based on Jianshan tunnel in Gansu Province, the special geological conditions such as high ground stress and weak interbedded surrounding rock make the excavation of tunnel easy to produce large deformation. In this article, the software finite difference software FLAC3D was used to establish numerical models and select the best construction method by comparing the deformation of the tunnel under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…e garden attached to a city hospital is a garden that provides specific rehabilitation treatment for patients by using the healthy plant theory and the theory of Yin and Yang and the five elements. In addition, most health gardens in China are aimed at healthy and sub healthy people, including health gardens, health squares, gardens, and so on [5]. Wanli City Ecological Community Wellness Park is a ginkgo ecological wellness forest where people and nature live in harmony.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e garden attached to a city hospital is a garden that provides specific rehabilitation treatment for patients by using the healthy plant theory and the theory of Yin and Yang and the five elements. In addition, most health gardens in China are aimed at healthy and sub healthy people, including health gardens, health squares, gardens, and so on [5]. Wanli City Ecological Community Wellness Park is a ginkgo ecological wellness forest where people and nature live in harmony.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To solve the problems of large soft rock deformation in tunnels under high-ground stress, Ref. [20] applied FLAC 3D to perform numerical simulations of various tunnel excavation schemes, based on Jianshan tunnel in the Gansu province. It showed that the three-bench tunnelling temporary inverted arch and three-step overhang method mostly controlled the surrounding rock's deformation effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [19,20] compared the control effect of the three-bench method and the pilot tunnel expansion method on the large deformation of soft rock combined with field tests and numerical simulations for the strongly weathered carbonaceous slate tunnel and optimized the existing tunnel construction scheme. Fang et al [21] used numerical simulations to explore a suitable excavation method for interbedded soft rock tunnels and pointed out that the three-bench temporary invert method had a better effect in controlling tunnel deformation, while the three-bench method had higher construction efficiency. It was suggested that the two methods should be used in combination in actual engineering excavation.…”
Section: Introductionmentioning
confidence: 99%